2018
DOI: 10.3138/canlivj.1.2.002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of hepatitis C virus infection: a tool for engagement with people who inject drugs in Vancouver’s Downtown Eastside

Abstract: Background Vancouver’s Downtown Eastside (DTES) faces the interrelated challenges of poverty, homelessness, mental health, addiction, and medical issues such as hepatitis C virus (HCV). This study evaluates a new model of engagement with people who inject drugs (PWID) in the DTES. Methods Our centre has developed the community pop-up clinic (CPC) to engage vulnerable populations such as PWID. Rapid HCV testing is offered using the OraQuick saliva assay. If a test is positive, immediate medical consultation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
2
13
1
Order By: Relevance
“…HCV treatment uptake and documented cure was suboptimal in the current study and lower than DAA therapy uptake of 61% among a population of PWID in Vancouver, Canada . Notably, in this study by Alimohammadi et al, a significant proportion of those not initiating treatment were homeless .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…HCV treatment uptake and documented cure was suboptimal in the current study and lower than DAA therapy uptake of 61% among a population of PWID in Vancouver, Canada . Notably, in this study by Alimohammadi et al, a significant proportion of those not initiating treatment were homeless .…”
Section: Discussionsupporting
confidence: 89%
“…HCV treatment uptake and documented cure was suboptimal in the current study and lower than DAA therapy uptake of 61% among a population of PWID in Vancouver, Canada . Notably, in this study by Alimohammadi et al, a significant proportion of those not initiating treatment were homeless . Although treatment uptake in the current study was higher than that (32%) among a sample of PWID in Australia in a study by Butler et al, unstable housing was found to be significantly associated with no treatment uptake .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The Cure‐it programme's progress was also affected by many factors related to patients such as poverty, unstable housing, active drug use and legal issues. In several previous studies, these factors were reported as barriers to receiving HCV treatment in both interferon‐based and DAA treatment . There are out of pocket costs for PCP’s consultation, filling the script and costs related to transportation, which some patients may not be able or wish to pay .…”
Section: Discussionmentioning
confidence: 99%
“…Patients’ active drug use and cycling through the criminal justice system were experienced as a barrier that places HCV treatment low in the patients’ list of priorities. Other studies noted that some patients who were using drugs were less likely to initiate and adhere to HCV treatment . Although a recent systematic review showed that PWIDs were able to successfully engage with DAA treatment, it was acknowledged that the included studies in the review had different definitions for recent drug use and many studies provided various adherence supports to improve patients’ engagement with the treatment .…”
Section: Discussionmentioning
confidence: 99%